Pengaruh Umur Perusahaan, Ukuran Perusahaan, Reputasi Auditor, Dan Pergantian Auditor - Ranti Dewi Fortuna; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2020)
The purpose of this study is to analyze the influence of company age, company size, auditor reputation and auditor change on auditor switching. The data used in this study are annual and financial reports on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2014-2018 period. The method of sampling data using purposive sampling method based on certain criteria. Based on the sampling method, a sample of 230 companies was obtained. Testing the hypothesis in this study using multiple linear regression analysis. The results showed that company size, auditor reputation and auditor switching had no effect on audit report lag and company age had a positive effect on audit report lag.